Evolutionary algorithm-driven screw press design - David Fait; Pavel Karban; Petra Hofrichterová (International Journal of Sustainable Engineering)
This paper explores the integration of evolutionary algorithms (EAs) into the process of designing manufacturing machines. The goal is to partially substitute the work of the human designer with modern artificial intelligence methods. The study focuses on the application of ISRES (Improved Stochastic Ranking Evolution Strategy) to design a screw press. The first part of the text is dedicated to a literature review and the search for a similar application. The field of manufacturing machines is quite conservative and even in the context of the whole of mechanical engineering only a few similar research papers have been found. The next paragraph deals with the calculation methodology and a basic description of a screw press. The background calculation model is described in the next chapter. The paper then proceeds with the principles of evolutionary algorithms and leads on to the optimisation process. The last part deals with the connection to a CAD (Computer Aided Design) program. The paper then concludes with the advantages and possible impact in the context of mechanical engineering.